If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -1(y + 5)) + 5 + x = 24 + yx Reorder the terms: (y + -1(5 + y)) + 5 + x = 24 + yx (y + (5 * -1 + y * -1)) + 5 + x = 24 + yx (y + (-5 + -1y)) + 5 + x = 24 + yx Reorder the terms: (-5 + y + -1y) + 5 + x = 24 + yx Combine like terms: y + -1y = 0 (-5 + 0) + 5 + x = 24 + yx (-5) + 5 + x = 24 + yx -5 + 5 + x = 24 + yx Combine like terms: -5 + 5 = 0 0 + x = 24 + yx x = 24 + yx Solving x = 24 + xy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1xy' to each side of the equation. x + -1xy = 24 + xy + -1xy Combine like terms: xy + -1xy = 0 x + -1xy = 24 + 0 x + -1xy = 24 Reorder the terms: -24 + x + -1xy = 24 + -24 Combine like terms: 24 + -24 = 0 -24 + x + -1xy = 0 The solution to this equation could not be determined.
| 9t+3=7t+9 | | -6-8(-5x-8)=98 | | 5-f=6 | | 123=4(1-6x)-1 | | (y-(y+5))-5+x=24+yx | | 2x+2y+4x+4y=0 | | 3x+3=10x+11 | | x-6x-1=15-x | | 8=3(m-7)+2 | | 15(3x-2)=6x-7 | | 20x+5y=15fory | | .25+40=.45+.25 | | -2y=-15 | | -8a-13=-4a+7 | | 2x+x+3+2x+1=70 | | 2x+x+3+2x+1=43.75 | | X+1x=47 | | 2x+x+3+2x+1=35 | | 6h-4=3h+5 | | 2x+x+3+2x+1=17.5 | | -2-8(7+4v)=-282 | | 5Y+8y=39 | | 6x-12+5x=2x+24 | | -(x+3)=5 | | X+x+1=47 | | a+b=-6 | | (3x-10)-5=-1 | | 10j-5j-j=16 | | (y*0)+x=24+yx | | -17.2k+4(-3+1.3k)=36 | | 553=265+48n | | (x+97)=(2x+32) |